Materialism Construction: Keyword Analysis of Bruno Mars’ Song Lyrics - Thongnopphakhun, Arisara; Trakulkasemsuk, Wannapa; Bunsom, Thanis (Journal of Studies in the English Language, 2019)
Music has long been an effective way to communicate to the masses, and lyrics play an essential role in delivering this communication. Lyrics may contain an ideology and influence listeners. This study aims to conduct a keyword analysis to investigate the materialistic ideology connoted in Bruno Mars’ song lyrics. The corpus of Bruno Mars’ lyrics was compiled from lyrics of 30 Bruno Mars songs in three albums released between 2010 and 2016. The corpus was then compared against the British National Corpus (BNC) to obtain a keyword list. The top 100 keywords were selected based on their statistical values for further analysis. They were classified according to their part of speech, and concordance lines of each keyword were obtained so as to discuss the representation of Bruno Mars’ songs. Materialistic concepts found in the corpus include an emphasis on, or preference for, luxury objects, brand-name items, a lavish lifestyle, parties, economic power, physical appearance, and objectifying women.